1987
DOI: 10.1210/endo-121-6-2035
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin Fraction 5 Stimulates Prolactin and Growth Hormone Release from Anterior Pituitary Cellsin Vitro*

Abstract: Thymosin fraction 5 (TF5) is a partially purified extract of bovine thymus containing 40-60 peptides. In addition to its well documented immunopotentiating effects, TF5 reportedly modulates the secretion of some hypothalamic peptides and pituitary hormones. In this study, TF5 (10-100 micrograms/ml) stimulated PRL release from normal, MtTW15, and 7315a cells and GH release from normal and MtTW15 cells, but had no apparent effect on LH release. No changes in intracellular cAMP or cGMP levels could be correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 24 publications
0
20
1
1
Order By: Relevance
“…Indeed, neonatal thymectomized and prepubertal congenitally athymic nude mice exhibit significantly lower levels of various pituitary and hypothalamic hormones, including gonadotropins and LHRH [4,15,16,38,39]. Thymic peptides modulate the production of classic hormones and neuropeptides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, neonatal thymectomized and prepubertal congenitally athymic nude mice exhibit significantly lower levels of various pituitary and hypothalamic hormones, including gonadotropins and LHRH [4,15,16,38,39]. Thymic peptides modulate the production of classic hormones and neuropeptides.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, LHRH is suggested to have not only a central effect but also to be involved in autocrine or paracrine regulation of the immune response. In turn, it has been clearly demonstrated that immune-derived mediators provide molecular signaling to the hypothalamo-hypophyseal system in adult mammals [15,16]. However, little is known about the role of LHRH in the development of immunity and the role of thymus peptides in the development of the hypothalamus during early ontogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been further demonstrated that TF5 stimulates corticotropin-releasing hormone release from mediobasal hypothalamus in vitro [23] and ACTH release from cultured rat pituitary cells [24], but does not affect glucocorticoid release from isolated adrenal fasciculata cells [25]. Also, TF5 has been shown to stimulate the release of PRL and GH from rat pituitary cells in vitro [26] as well as immunoreactive ß-endorphin and ACTH from mouse corticotropic tumor cells [27][28][29].…”
Section: Thymosin Peptides As Immunotransmittersmentioning
confidence: 99%
“…It has been further demonstrated that TF5 stimulates CRH release from MBH in vitro [41] and ACTH release from cultured rat pituitary cells [42] but does not affect glucocorticoid release from isolated adrenal fasciculata cells [43]. Also, TF5 has been shown to stimulate the release of PRL and GH from rat pituitary cells in vitro [44] as well as immunoreactive ß-endorphin and ACTH from mouse corticotropic tumor cells [45][46][47].…”
Section: Thymosin Peptides As Immunotransmittersmentioning
confidence: 99%